Application on Hypergraph in Vigenere Chiper - Asari, Okta Endri; Dafik, Dafik; Adawiyah, Robiatul; Kristiana, Arika Indah; Prihandini, Rafiantika Megahnia (Universitas Muhammadiyah Mataram, 2026)
Message protection remains a major focus in the field of cryptography. This study proposes a new development on the Caesar cipher algorithm by utilizing hypergraph as a keystream generation source. The research designs a super (a,d)-hyperedge antimagic total labeling method applied to three hypergraph structures (Volcano, Semi Parachute, and Comb) to generate the keystream. Security is evaluated using four mechanisms: brute force analysis, processing time, ciphertext character distribution, and ciphertext bit size. The findings prove that the hypergraph based approach is robust against brute force attacks, improve memory and time efficiency. Quantitatively, the Comb hypergraph demonstrates the best efficiency, achieving an encryption time of 0.0030 seconds for 512 bytes and superior storage efficiency (e.g., 136 bytes for 16 bytes ), outperforming the Semi Parachute and Volcano structures. The main contributions include the hypergraph labeling-based keystream generation algorithm, dynamic block key construction, and a Vigenere protocol that is more adaptive to storage constraints and computationally efficient..